The effectiveness of teaching word etymology on vocabulary retention among EFL students - Mukhtasarkhon Bakhtiyor qizi, Rakhimjonova; Sultonova , Nigora Abduganievna (The Lingua Spectrum, 2026)
This article investigates the effectiveness of etymological instruction as a cognitive strategy to enhance vocabulary recall. Through integrating etymology with language learning strategies students not only be able to use it theoretically, at the same time the information appears as practical and make it easy to use. Vocabulary plays a critical role in language learning, but considered as one of the most time-consuming procedures. As most of the students struggle to retrieve the given vocabulary after some time, learning its etymology could enhance their vocabulary skills as well as comprehension rather than memorizing it blindly (Hussein & Faris, 2022). Through integrating etymology with other vocabulary learning tactics students can be able to retrieve the word in their long-term memory. It helps them to learn about the core of the words along with understanding the meaning in context based on the roots, which makes the language usage flexible and easy to get the gist in any content.